Implementing Serial Picture Media Within a Problem-Based Learning Framework to Enhance Indonesian Language Learning Outcomes for Third-Grade Students - Marshela Handoko Putri; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto; Ryzca Siti Qomariah (International Journal of Educational Research, 2026)
This study investigates the development of Indonesian language literacy among third-grade elementary school students. The primary problems identified were acute classroom passivity and low reading comprehension, evidenced by an initial learning mastery of only 45.16%, which were largely driven by conventional teacher-centered pedagogy. The objective of this research is to enhance early-grade reading literacy and active participation through an innovative instructional intervention. The proposed method employed a two-cycle Classroom Action Research (CAR) design at SDN Jrebeng Kulon 1, integrating the Problem-Based Learning (PBL) model assisted by serial picture media. This approach utilizes chronological visual scaffolding to facilitate narrative comprehension for students in the concrete operational stage. The results demonstrated a highly significant academic progression: classical learning mastery increased to 70.97% (mean score: 80.80) in Cycle I and culminated in an absolute 100% mastery rate (mean score: 94.51) by the end of Cycle II. The synthesis of these findings reveals that transitioning from static visual aids to serial visual stimuli within a problem-oriented framework effectively mitigates cognitive dissonance and eradicates classroom passivity. In conclusion, the integration of the PBL model with serial picture media serves as a comprehensive pedagogical solution that not only maximizes cognitive reading comprehension but also reconstructs students' verbal articulation and social-collaborative skills, offering a highly scalable strategy for early primary education.